TiO2/Chitosan bioplastic as Antibacterial of Stephylococcus aureus for Food Preservation - Kustiningsih, Indar; Barleany, Dhena Ria; Abriyani, Devi; Ridwan, Asep; Syairazy, Muhammad; Firdaus, Mochamad Adha (World Chemical Engineering Journal, 2021)
Nowadays, bioplastic development become hot trends to assess environmental issues. Many materials have been purposed to be the best resources for bioplastic manufacturing. Chitosan is one of the most abundant resources in which could derivates from biomaterial waste called chitin. TiO2 nanoparticles incorporation within biomaterial presumably not only enhance its mechanical properties but also improve biocompatibility of medical characteristic such as bacterial annihilation. From this study, it was shown that small amount of TiO2 nanoparticles within chitosan bioplastic prove improvement of both characteristic. Nevertheless, it was also slightly increasing material durability to degrade.